Potential Targets and Their Relevant Inhibitors in Anti-influenza Fields - Gong, Jianzhi; Fang, Hao; Li, Minyong; Liu, Yu; Yang, Kanghui; Liu, Yingzi; Xu, Wenfang (Current Medicinal Chemistry, 2009)
Influenza is a disease for deeply affecting millions of people every year. Recently, there has been considerable concern regarding the highly pathogenic H5N1 avian influenza virus, and its human pandemic potential. With developments in viral biology, there are more novel antiviral strategies targeting these viruses. In this review, we will discuss several proven and potential anti-influenza targets, including viral factors (such as hemagglutinin (HA), M2 ion channel protein, RNA-dependent RNA polymerase (RdRp), nucleoprotein (NP), non-structural protein (NS) and neuraminidase (NA)) and host factors (such as v-ATPase, protease, inosine monophosphate dehydrogenase (IMPDH) and intracellular signalling cascades), and their relevant inhibitors.
Keywords: target